Simulation-based optimization of control policy on multi-echelon inventory system for fresh agricultural products - Xu, Guangyin; Feng, Jihao; Chen, Fenglei; Wang, Heng; Wang, Zhenfeng (International Journal of Agricultural and Biological Engineering, 2019)
As fresh agricultural products are perishable and vulnerable, reducing inventory cost is a strategic target for supply chain enterprises. How to design a reliable multi-echelon inventory control policy is still a great challenge. Therefore, the inventory cost of a three-level fresh agricultural products inventory system was firstly mathematically analyzed. Then, the simulation-based optimization model of the multi-echelon inventory system for fresh agricultural products was proposed by using the Flexsim simulation software and the improved particle swarm optimization algorithm. Finally, the multi-echelon inventory system is simulated based on a large number of survey data. Simulation results demonstrate that the proposed simulation-based optimization model of multi-echelon inventory system for fresh agricultural products can provide decision-making and technical support for the formulation of inventory control policy, and also it shows that the modeling of system simulation is an effective method to solve the problem of complex system. Keywords: multi-echelon inventory system, simulation-based optimization, fresh agricultural products, control policy, Flexsim simulation software DOI: 10.25165/j.ijabe.20191202.2834 Citation: Xu G Y, Feng J H, Chen F L, Wang H, Wang Z F. Simulation-based optimization of control policy on multi-echelon inventory system for fresh agricultural products. Int J Agric & Biol Eng, 2019; 12(2): 184–194.